Neuroimaging Features of Optic Nerve Hemangioblastoma Identified by Conventional and Advanced Magnetic Resonance Techniques: A Case Report and Literature Review - Duan, Meihan; Yang, Lie; Kang, Jun; Wang, Renzhi; You, Hui; Feng, Ming (Frontiers in Oncology, 2021)
Optic nerve hemangioblastoma is a very rare benign tumor which has only been reported in 39 cases by now. Appearing to be hyperintense on T2-weighted imaging with a significant enhancement on contrast scans, it is usually misdiagnosed as glioma or meningioma due to similar magnetic resonance imaging (MRI) manifestations. Herein, we firstly report an optic nerve hemangioblastoma case employing advanced magnetic resonance techniques including diffusion-weighted imaging (DWI), apparent diffusion coefficient (ADC) maps and magnetic resonance angiography (MRA). In addition, we collect all published optic nerve hemangioblastoma cases and review their neuroimaging findings from MRI and angiography. The results show that the solid type is dominant in optic nerve hemangioblastoma and extensive edema is widely observed. This is surprisingly contrary to our impression of hemangioblastoma summarized from cerebellar lesions. Besides the structural features, some quantificational indexes such as ADC and relative cerebral blood volume (rCBV) ratio which are extremely high in cerebellar hemangioblastoma may also improve the preoperative diagnosis of optic nerve hemangioblastoma. Based on the neuroimaging features, we discuss the critical points in the differential diagnosis between optic nerve hemangioblastoma from some easily-confused diseases such as optic pathway glioma and optic nerve sheath meningioma.